Common Mycorrhizal Network Induced JA/ET Genes Expression in Healthy Potato Plants Connected to Potato Plants Infected by Phytophthora infestans - Alaux, Pierre-Louis; Naveau, Françoise; Declerck, Stéphane; Cranenbrouck, Sylvie (Frontiers in Plant Science, 2020)
Most plants are connected belowground via common mycorrhizal networks (CMNs). In their presence, the transmission of warning signals from diseased to uninfected plants has been reported. However, current studies have all been conducted in pots making it difficult to discriminate direct from indirect contribution of hyphae to the transmission of the signals. Here, we conducted an in vitro study with potato plantlets connected by a CMN of the arbuscular mycorrhizal fungus Rhizophagus irregularis. The plantlets were grown in physically separated compartments and their connection ensured only by the CMN. The donor potato plantlets were infected by Phytophthora infestans and defense genes analyzed 24, 48 and 120 h post-infection (hpi) in the uninfected receiver potato plantlets. Twenty-four hpi by the pathogen, PAL, PR-1b, ERF3 and LOX genes were significantly up-regulated, whereas no significant transcript variation was noticed 48 and 120 hpi. The exact nature of the warning signals remains unknown but was not associated to microorganisms other than the AMF, diffusion mechanisms through the growth medium or induced by volatile compounds. The defense response appeared to be transitory and associated with the jasmonic acid or ethylene pathway. These findings demonstrate the direct involvement of hyphae in the transmission of warning signals from diseased to uninfected potato plantlets and their indubitable role in providing a route for activating defense responses in uninfected plants.